Indoleamine 2,3-Dioxygenase Expression Pattern in the Tumor Microenvironment Predicts Clinical Outcome in Early Stage Cervical Cancer - Heeren, A. Marijne; van Dijk, Ilse; Berry, Daniella R. A. I.; Khelil, Maryam; Ferns, Debbie; Kole, Jeroen; Musters, René J. P.; Thijssen, Victor L.; Mom, Constantijne H.; Kenter, Gemma G.; Bleeker, Maaike C. G.; de Gruijl, Tanja D.; et al. (Frontiers in Immunology, 2018)
The indoleamine 2,3-dioxygenase (IDO) enzyme can act as an immunoregulator by inhibiting T cell function via the degradation of the essential amino acid tryptophan (trp) into kynurenine (kyn) and its derivates. The kyn/trp ratio in serum is a prognostic factor for cervical cancer patients, however, information about the relationship between serum levels and IDO expression in the tumor is lacking. IDO expression was studied in 71 primary and 14 paired metastatic cervical cancer samples by various immunohistochemical (IHC) techniques, including 7-colour fluorescent multiparameter IHC, and the link between the concentration of IDO metabolites in serum, clinicopathological characteristics, and the presence of (proliferating) T cells (CD8, Ki67, and FoxP3) was examined. In addition, we compared the relationships between IDO1 and IFNG gene expression and clinical parameters using RNAseq data from 144 cervical tumor samples published by The Cancer Genome Atlas (TCGA). Here we demonstrate that patchy tumor IDO expression is associated with an increased systemic kyn/trp ratio in cervical cancer (P=0.009), whereas marginal tumor expression at the interface with the stroma is linked to improved disease-free (DFS, P=0.017) and disease-specific survival (DSS, P=0.043). The latter may be related to T cell infiltration and localized IFNγ release inducing IDO expression. Indeed, TCGA analysis of 144 cervical tumor samples revealed a strong and positive correlation between IDO1 and IFNG mRNA expression levels (P<0.001) and a significant association with improved DFS for high IDO1 and IFNG transcript levels (P=0.031). Unexpectedly, IDO+ tumors had higher CD8+Ki67+ T cell rates (P=0.004). Our data thus indicate that the serum kyn/trp ratio and IDO expression in primary tumor samples are not clear-cut biomarkers for prognosis and stratification of early stage patients with cervical cancer for clinical trials implementing IDO inhibitors. Rather, a marginal IDO expression pattern in the tumor dominantly predicts favorable outcome, which might be related to IFNγ release in the cervical tumor microenvironment.